50 years of decoding olfaction. (November 2018) - Brennan, Peter A
The identification, in the late 20th century, of unexpectedly large families of G-protein-coupled chemosensory receptors revolutionised our understanding of the olfactory system. The discovery that non-selective olfactory sensory neurons express a single olfactory receptor type and project to a specific glomerulus in the main olfactory bulb provided fundamental insight into the spatial pattern of odour representation in the main olfactory bulb. Studies using head-fixed awake mice and optogenetics have revealed the importance of the timing of glomerular input in relation to the sniff cycle and the role of piriform cortex in odour object recognition. What in the 1970s had appeared to be a relatively simple dichotomy between odour detection by the main olfactory system and pheromone detection by the vomeronasal system has been found to consist of multiple subsystems. These mediate innate responses to odours and pheromones and to substances as diverse as O2, volatile urinary constituents, peptides and proteins.